A Competence Model for Environmental Education. (November 2014) - Roczen, Nina; Kaiser, Florian G.; Bogner, Franz X.; Wilson, Mark
The goal of environmental education is ultimately to enable a person to strive for and to attain a more ecological way of life. In this article, we begin by distinguishing three forms of environmental knowledge and go on to predict that people's attitude toward nature represents the force that drives their ecological behavioral engagement. Based on data from 1, 907 students, we calibrated previously established instruments to measure ecological behavior, environmental knowledge, and attitude toward nature with Rasch-type models. Using path modeling, we corroborated our theoretically anticipated competence structure. While environmental knowledge revealed a modest behavioral effect, attitude toward nature turned out to be, as expected, the stronger determinant of behavior. Overall, we propose a competence model that has the potential to guide us into more evidence-based ways of promoting the overall ecological engagement of individuals.